(untitled) (African Journal of Biomedical Research, 2020)
No matter the complexity of a clinical research, one critical component that serves as bridge between conceptualization of research idea and the eventual publication of findings is data management. It encapsulates the whole processes involved in managing the life cycle of data in a clinical research project. Data management can make or mar any research. For example, a research with scientifically sound design but poor, incoherent data management procedure would end up with poor quality data. In this article, the author provides a brief overview of key considerations for data management in clinical research